Production of EPSPS and bar gene double-herbicide resistant castor (Ricinus communis L.). Issue 1 (1st January 2020) - Zhao, Huibo; Zhao, Yong; Luo, Rui; Yang, Lifeng; Li, Guorui; Di, Jianjun; Peng, Mu; Li, Lili; Wen, Qi; Liang, Xiaotian; Yin, Mingda; Wen, Yanpeng; et al.
Abstract: Castor ( Ricinus communis L.) is one of the world's top ten oil crops. China is the second largest producer of castor beans, but China's castor bean acreage has been declining. A principal reason for this decline is the prevalence of weeds and the absence of herbicide resistant varieties of castor plants. In this study, we used Agrobacterium-mediated gene transfer to introduce the EPSPS (5-enolpyruvylshikimate-3-phosphate synthase) gene, which confers resistance to glyphosate, and the Bar (phosphinothricin N-acetyltransferase) gene, encoding resistance to glufosinate, into castor 2129 (high stem excellent recovery line) and CSR 181 (dwarf stem excellent recovery line). The transgenic plants exhibited significantly increased expression of the EPSPS and Bar genes and significantly increased resistance to glyphosate and glufosinate. Proteomic analysis showed differences in the amounts of 20 proteins in the dwarf stem transgenic plants. Nine of these proteins are involved in photosynthesis and indirectly related to the mechanism of action of the Bar gene. Eight proteins are involved in defense, repair, stress response, oxidative phosphorylation, and metabolic pathways and are indirectly related to the mechanism of action of the EPSPS gene. These results provide a foundation for the preparation of high herbicide resistant castor varieties.